CD5-positive, Small B-Cell Lymphoproliferative Disorders: Aberrant Findings of CLL/SLL and MCL - Hu, MD, Youjun; Golightly, PhD, Marc (North American Journal of Medicine and Science, 2010)
Most common CD5-positive, small B cell lymphoproliferative disorders include chronic lymphocytic leukemia/small lymphocytic lymphoma (CLL/SLL) and mantle cell lymphoma (MCL). Among these cases, atypical morphology, immunophenotype, and/or cytogenetic abnormalities are not uncommon. As an aberrant marker, CD5 expression is not limited to the cells of CLL/SLL or MCL and has been found in other B cell lymphomas ( both low grade and more aggressive types). CD5-negative CLL/SLL and MCL also are well documented, as are reports of other aberrant immunophenotypes of CLL/SLL and MCL. In addition, monoclonal B-cell lymphocytosis (MBL) of unknown significance has recently been reported in otherwise healthy individuals. We review here the findings that do not fulfill the current definitions of CLL/SLL or MCL. It is imperative that a pathologist should be familiar with these aberrant findings when considering CLL/SLL or MCL as a possible diagnosis. Furthermore, these aberrant findings may be clues to further understanding these entities.